Consequences of Soil Crude Oil Pollution on Some Wood Properties of Olive Trees - Hassan H. Ali (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
To enlighten the extent of crude oil pollution effects on some anatomical characteristics of olive plant (Olea europaea ). Two years - old seedlings were chosen to grow under 5 levels of pollution (0.0, 0.5, 1.0, 2.0, and 3.0, liter/ plant). The experiment has been conducted in the experimental field of Natural History Research Center and Museum, University of Baghdad. It was designed as CRD experiment. Testing wood specimens were prepared after 2.5 years of growth. Fiber length, width, wall thickness, and wood specific gravity were measured. Results showed that olive plants could not resist the highest level ( 3 liters / plant ) of pollution .Fiber length was the most  affected property by treatment. All fiber dimensions were decreased with the increase of pollution level. The reduction was unsystematic. 12% of the fiber length was reduced as a result of pollution. Wood specific gravity of polluted plants showed few higher values than that of control. Lower parts of stem seemed to be more affected, that may be because these parts are fare away from crown ( the source of oxen ).